2022
DOI: 10.3390/cells11132085
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Autophagy as a Regulator of Melanin Homeostasis

Abstract: Melanosomes are melanocyte-specific organelles that protect cells from ultraviolet (UV)-induced deoxyribonucleic acid damage through the production and accumulation of melanin and are transferred from melanocytes to keratinocytes. The relatively well-known process by which melanin is synthesized from melanocytes is known as melanogenesis. The relationship between melanogenesis and autophagy is attracting the attention of researchers because proteins associated with autophagy, such as WD repeat domain phosphoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 103 publications
0
28
0
Order By: Relevance
“…These results suggested that the basal levels of autophagy might be lower in UM cells, than in normal choroidal melanocytes. The most research on uveal melanocytes have been focused on retinal pigmented epithelium, however, the loss of melanosomes in aged choroidal melanocytes has previously been shown (Nag, 2015), which can at least in part be explained by the fact that autophagy machinery proteins may be involved in melanogenesis regulation (Lee et al, 2022). Autophagy participates in the process of melanogenesis and plays a major role in the redox homeostasis of melanocytes; furthermore, impairment of autophagy might disrupt the antioxidant defense system, which leads to oxidative damages of melanocytes (Jeong et al, 2020;Qiao et al, 2016Qiao et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the basal levels of autophagy might be lower in UM cells, than in normal choroidal melanocytes. The most research on uveal melanocytes have been focused on retinal pigmented epithelium, however, the loss of melanosomes in aged choroidal melanocytes has previously been shown (Nag, 2015), which can at least in part be explained by the fact that autophagy machinery proteins may be involved in melanogenesis regulation (Lee et al, 2022). Autophagy participates in the process of melanogenesis and plays a major role in the redox homeostasis of melanocytes; furthermore, impairment of autophagy might disrupt the antioxidant defense system, which leads to oxidative damages of melanocytes (Jeong et al, 2020;Qiao et al, 2016Qiao et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is required for AMP-activated protein kinase (AMPK) activation and inactivation of mTOR's target [53]. In addition, LC3B-II, an important protein marker in autophagy, induces ERK activation; ERK increases MITF expression via CREB phosphorylation; and ATG7 and Beclin-1 are positively related to MITF expression and MITF transcriptional activity, respectively [54]. To investigate EG autophagy-enhancing activity, AKT, mTOR, Beclin, and LC3B autophagy markers were induced by treating B16F10 cells with MSH, and the protein expression patterns were then measured.…”
Section: Effect Of Eg On Antimelanogenesis-related Proteins/genes And...mentioning
confidence: 99%
“…Juss extract prevented melanogenesis and induced autophagy via autophagy markers LC3B and p62 [10]. A study described a mechanism underpinning the regulation of melanin synthesis or function in antiaging, finding that autophagy responded in accordance with AKT2 concentrations [54].…”
Section: Effect Of Eg On Antimelanogenesis-related Proteins/genes And...mentioning
confidence: 99%
“…Therein, MITF can also regulate the expression of TYR, TYRP-1, DCT, Pmel17, Rab27 and bcl-2. All these genes have an important function on melanocytes differentiation, dendricity, proliferation and apoptosis, as well as melanin synthesis (Hwang et al, 2017;Lee et al, 2022).…”
Section: The Synthesis Of Melaninmentioning
confidence: 99%
“…Furthermore, many signal pathways are involved in regulating MITF. Whitening active ingredients can affect the level of MITF by regulating the above signal pathways, further inhibit the expression of tyrosinase, so as to achieve skin whitening (Abrahamian & Grimm, 2021;Lee et al, 2022). DHA and EPA can inhibit the synthesis of melanin (Yamada et al, 2019).…”
Section: Inhibiting the Synthesis Of Melaninmentioning
confidence: 99%